47 TUMOR NECROSIS FACTOR-α-DEPENDENT PATHWAYS MODULATE β-ADRENERGIC RECEPTOR-MEDIATED MYOCARDIAL HYPERTROPHY IN VIVO. (1st March 2005) - Garlie, J. B.; Gu, Y.; Luo, J.; Ortines, R.; Srivastava, S.; Chandrasekar, B.; Cardwell, E.; Prabhu, S. D.
Abstract : We have previously shown that sustained β-adrenergic receptor (β-AR) activation, as occurs in heart failure, induces myocardial tumor necrosis factor (TNF)-α expression. However, the pathophysiologic role of such TNF-α induction in β-AR-mediated cardiac remodeling is unknown. Accordingly, we tested the hypothesis that TNF-α dependent pathways contribute importantly to β-AR-induced hypertrophy. Osmotic minipumps with either isoproterenol (ISO, 12.5 mg/kg/hr) or saline (SAL) were placed in 10-week wild-type (WT) C57/B6 (n = 17), TNF-α receptor-1 (TNFR1) knockout (KO) (n = 10), or TNFR2 KO (n = 10) mice for 7 days. Evaluation was performed via echocardiography, left-ventricular (LV) pressure-volume inductance catheterization, tissue morphology and nuclear DNA-binding studies. Functional studies of WT ISO mice (vs. SAL) revealed pathophysiologic changes consistent with concentric hypertrophy and enhanced diastolic function, including significant (p<0.01) increases in heart rate, velocity of circumferential fiber shortening (Vcf), relative wall thickness, and dP/dtmax (13682 ± 1101 vs. 6625 ± 825 mm Hg/s). WT ISO hearts also demonstrated significant hypertrophy, morphologically and biochemically, with increased (p<0.05) LV weight/tibia length (TL) ratio and a 4-fold increase in atrial natriuretic factor (ANF) mRNA (p<0.01). TNFR1 KO ISO mice demonstrated mechanical and morphometric changes similar to WT ISO mice and comparable increases in ANF mRNA. In contrast, TNFR2 KO ISO mice had an exaggerated hypertrophic response versus WT ISO with 1) greater wall thickness (p<0.025), 2) greater heart weight/TL ratio (5.92 ± 0.56 vs. 5.26 ± 0.39, p<0.05), and 3) a trend towards greater ANF mRNA levels. TNFR2 KO mice also showed attenuation of ISO-mediated contractile enhancement compared to TNFR1 KO (Vcf 13.2 ± 1.5 vs. 15.7 ± 2.1 circ/s, p<0.05). DNA binding assays were used to determine the effects of selective TNFR ablation on downstream signaling. No change in activated nuclear factor (NF)-κ-B (p65 subunit) was seen among any of the experimental groups. Conclusion: TNFR2 signaling attenuates the hypertrophic response and enhances the contractile response to chronic β-AR activation, an effect independent of NF-κ-B activation. TNFR1 signaling, however, does not seem to modulate the LV hypertrophic response during β-AR stimulation. Analogous interplay between the β-AR and TNFR signaling pathways may occur in the failing heart.